Spectroscopic methods in mineralogy and materials sciences - Henderson, Grant Stephen, 1956-; Neuville, Daniel R.; Downs, Robert T., 1955- (Reviews in mineralogy and geochemistry, 2014)
A complement to Spectroscopic methods in mineralogy and geology, edited by Frank Hawthorne in 1988, vol. 18 of the Reviews in mineralogy series. This current work also updates many of the techniques mentioned in the original volume along with introducing new methods in spectroscopy that had developed in the past twenty-five years.